(untitled) (Mustansiria Dental Journal, 2025)
Background: Propolis is a natural resin produced by bees from plant exudates, combined with pollen, wax, and enzymes. It is known for its antibacterial and anti-inflammatory properties. Plaque is a yellowish white or grayish substance that adheres firmly to the surfaces of teeth and other complex structures in the mouth. The study aimed to evaluate the effects of lozenges containing propolis on the levels of Interleukin-10 (IL-10) and plaque accumulation. Method: A prospective cohort interventional case-control clinical trial. A total of 80 patients were divided into two groups: 40 participants in the case group and 40 in the control group. Participants in the case group received propolis lozenge extract after a baseline saliva sample was collected and the Plaque Index was measured. They were instructed to use the lozenge twice daily for 7 days, once in the morning and once in the evening. In contrast, the control group received only oral hygiene instructions. During the second visit, saliva samples were collected again, and the Plaque Index (PI) was measured. Result: The case group observed significant differences between the two visits regarding the mean Plaque Index (PI), whereas the control group did not show significant changes. Additionally, significant differences were found in the mean levels of interleukin-10 in the case group.